Tracktivism: Eco-activist walking art as expanded choreography in rural landscape. Issue 2 (1st December 2019) - Allen, Jess
AbstractThis article offers a reflexive account of my journey from dance into walking art through a methodological examination of tracktivism: the rural, eco-activist, pedestrian performance practice I have developed over the past eight years. My dancer's perception of walking art in the sculptural tradition had always been as choreography on an expanded scale: bringing attention to spatial patterns in landscape through the 'stylus' of the walking body. Here I examine the ways in which the growing oeuvre of tracktivist works have employed this choreographic device to (re)frame walking art as eco-activist performance. I consider how an art walk may be shaped in such a way as to foreground the spatial nature of ecological dis/connection in working agricultural landscapes, giving examples from my practice. I also propose that as patterns or routes expressly designed to be walked, the performer's material body becomes a 'measurant' to calibrate human scale against planetary scale. Thus the practice might be perceived to function as emancipated eco-activist choreography that offers a means of revealing and embracing our ecological enmeshment with/in complex more-than-human flows.